The database Sweden 1570-1810: population, agriculture, land ownership - Agricultural statistics on parish level, 1570 - Andersson Palm, Lennart (University of Gothenburg, 2013)
From an international point of view, Sweden has some partially unique historical statistics, including, among other things, statistics on population growth from 1749 onwards. In the Swedish archives though, there are very rich sources of various kinds, which could provide statistics for periods much further back in time. It is especially important for agricultural statistics, since the official data is not reliable until as late as about 1900. Particularly valuable material in terms of population and agriculture is preserved from the periods around 1570, 1630, 1690. For the period around 1570 and 1630 there are tax records of the number of animals in each parish. As from the first half of the 1600s, it becomes increasingly common with data on the arable land in maps and land surveying descriptions. Around 1690 survey records and maps were established for tens of thousands of farms, in connection with the introduction of the so-called allotment system. From 1736 onwards, hundreds of thousands of inventories of farmers have been preserved. They provide information about the deceased farmers’ animals and often on the seed corn. The sources also provide information on land ownership (taxed land, Crown land and land exempt from tax, owned by the nobility). For the former Danish and Norwegian districts (Halland, Blekinge, Skåne, Gotland, Bohuslän, Jämtland and Härjedalen) before Swedish times, partly other kinds of sources provide similar data.

Purpose:

The aim of the project is to create agricultural statistics covering all parishes within Sweden’s contemporary boundaries and the periods around 1570, 1630, 1690, 1750 and 1810, to supplement the population statistics for the same periods already published in 2000 (Lennart Palm, "The population of Swedish parishes and municipalities 1571-1997"). The agricultural statistics will provide easily accessible data for a large number of users, such as historians, economic historians, human geographers, geographers, sociologists, ethnologists, the County Administrative Board’s cultural environment planners, the staff of the Swedish National Heritage Board and of the county museums, as well as pupils working on school projects and local historians.

Sverige har en internationellt sett delvis unik historisk statistik, bl a över befolkningsutvecklingen från 1749 och framåt. I de svenska arkiven finns dock mycket innehållsrika källor av olika slag som skulle kunna föra statistiken mycket längre tillbaks i tiden. Särskilt viktigt är det för jordbruksstatistiken, där den officiella inte börjar bli pålitlig förrän så sent som cirka 1900. Särskilt värdefullt material vad gäller befolkning och jordbruk finns bevarat från perioderna cirka 1570, 1630, 1690. För tiden cirka 1570 och 1630 finns skattelängder över antalet djur socken för socken. Fr o m första halvan av 1600-talet blir det allt vanligare med åkeruppgifter i kartor och anda lantmäteribeskrivningar. Runt 1690 upprättades besiktningsprotokoll och kartor i för 10 000-tals gårdar i samband med införandet av det s k indelningsverket. Från 1736 och framåt har hundratusentals bouppteckningar efter bönder bevarats. De ger uppgifter om de avlidnas djur och ofta spannmålsutsäde. Källorna ger också uppgifter om jordägandet (det s k mantalets skatte-, krono- och frälsejord). För de f d danska och norska landskapen (Halland, Blekinge, Skåne, Gotland, Bohuslän, Jämtland och Härjedalen) före svensktiden ger delvis andra slags källor liknande uppgifter.

Syfte:

Projektet vill skapa en sockenvid jordbruksstatistik för Sverige inom nutida gränser och perioderna cirka 1570, 1630, 1690, 1750 och 1810 som kan komplettera den folkmängdsstatistik för samma perioder som redan publicerats år 2000 (Lennart Palm, "Folkmängden i Sveriges socknar och kommuner 1571-1997"). Denna jordbruksstatistik kommer att ge lättillgängliga data för en stor mängd användare, t ex historiker, ekonomhistoriker, kulturgeografer, geografer, sociologer, etnologer, länsstyrelsernas kulturmiljöplanerare, riksantikvarieämbetets och länsmuseernas personal, projektarbetande skolungdom, hembygdsforskare.
Agrarhistorisk databas 1570-1810: befolkning, jordbruk, jordägande - Sockenvis jordbruksstatistik för 1570
Keywords: population; befolkning; agriculture; lantbruk; farming; jordbruk; 16th century; 1500-tal; animal husbandry; boskapsskötsel; Early modern period; tidigmodern tid; 17th century; 1600-tal; 19th century; 1800-tal; forest; skog; 18th century; 1700-tal; HISTORY; HISTORIA; Probability Theory and Statistics; Sannolikhetsteori och statistik; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Agricultural Science; Jordbruksvetenskap; History and Archaeology; Historia och arkeologi; History; Historia